Evaluating bioactivity and bioaccessibility properties of the propolis extract prepared with L-lactic acid: An alternative solvent to ethanol for propolis extraction - Atayoğlu, Ali Timuçin; Sözeri Atik, Didem; Bölük, Esra; Gürbüz, Başak; Ceylan, Fatma Duygu; Çapanoğlu, Esra; Atayolu, Rümeysa; Paradkar, Anant; Fearnley, James; Palabıyık, İbrahim (Elsevier Ltd, 2023)
Ethanol readily solubilizes the active components of propolis. Due to certain disadvantages of ethanolic extracts, developing new non-ethanolic extraction methods is highly desirable. This study aimed to determine the content of phenolic compounds and antioxidant activity of propolis by using lactic acid extraction compared to ethanol. Various concentrations of ethanol and lactic acid were utilized to produce extracts, and an in vitro digestion procedure was applied to the extracts to compare the bioaccessibility of phenolic compounds by using LC-MS/MS in extracts and HPLC-DAD in digested samples. The compounds detected in the lactic acid-based propolis solution had similar values to those in the ethanol solution at a propolis concentration of 10%. The propolis-lactic acid solution had a significantly higher antioxidant activity against DPPH radical than the one prepared with ethanol at the same concentration (p < 0.05). Chrysin and naringenin were found as the most abundant phenolic compounds in the initial samples during in vitro digestion experiments. Pinocembrin was the most bioaccessible component among the dialyzed IN fractions of ethanol and lactic acid-based solutions, whereas some compounds were not detected. The results suggest that lactic acid may be used as an alternative to ethanol for propolis extraction.
Keywords: Antioxidant; Extraction; Lactic Acid; Phenolics; Propolis